FileMaker : practical techniques - Osborne, John (Infinite Skills, 2014)
"In this Practical Techniques in FileMaker training course, expert author John Osborne teaches you a number of useful techniques for working in the FileMaker database. This course assumes you have some working knowledge of FileMaker. You will start by learning how to work from scratch, then jump into learning about automation, including how to sort columns, create a custom message, and hide objects. John will teach you about table occurrences, calculations, and correspondence. This video tutorial also covers complex relationships, such as creating a links table, testing the basic construct, and cleaning up the interface. Finally, you will cover a number of other handy techniques, including how to find reminders, create a custom menu, and squash bugs. Once you have completed this computer based training video, you will have developed the skills necessary to apply these practical techniques while working in FileMaker. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.